(untitled) (Research, Society and Development, 2022)
Objective: to describe about the experience of students from the first period of the medical course at Universidade CEUMA, at the Basic Health Unit Dra. Maria Aragão, facing home visits and the importance of the multidisciplinary team in the unified health system. Methodology: This is a qualitative experience report, where a home visit was described. Three home visits were carried out in the area related to Parque Alvorada. The focus determined by the students is based on the first experience, in which it was possible to apply most of the concepts defined in the classroom theory. Results: The concepts of palliative care were discussed, as the patient in question had a critical prognosis. With this, the academics reported that medical care goes beyond care related to the cure of diseases, it involves the humanization of the doctor-patient relationship, having among its principles the exercise of solidarity, equity and empathy in medicine. In addition, it was discussed about the importance of the multidisciplinary team for effective care directed to the patient, through a holistic view. Final considerations: it is concluded that the practice of home visits provides vast practical knowledge, which cannot be equivalent to the examples seen in the theory of medical graduation. In this way, the benefits arising from such an experience are of unique significance, as they add important knowledge for a better professional and human formation.